2013
DOI: 10.1111/cpsp.12038
|View full text |Cite
|
Sign up to set email alerts
|

What, me worry and ruminate about DSM‐5 and RDoC? The importance of targeting negative self‐referential processing.

Abstract: Rumination, worry, and other forms of negative self-referential processing (NSRP) are familiar to everyone, as reflecting on the self is perhaps our most human characteristic. However, for a substantial subgroup of patients, NSRP arises in response to intense emotionality, worsening the clinical presentation, and diminishing the treatment response. The combination of emotionality and NSRP likely reflects an endophenotype of complicated and treatment refractory patients who fail to achieve a satisfactory treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
120
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 120 publications
(130 citation statements)
references
References 80 publications
6
120
0
4
Order By: Relevance
“…For example, Mennin and Fresco (2013) summarized empirical evidence suggesting that (1) comorbid anxiety and mood disorders are associated with greater rumination (Olatunji et al, 2013), and (2) those with comorbid anxiety and depression often have the poorest response to treatment (e.g., Farabaugh et al, 2010). As such, the authors suggest that those with high RNT may be least likely to respond to traditional CBT and may benefit from specifically targeting RNT in treatment (Mennin & Fresco, 2013). Thus, RNT-focused intervention may improve outcome for treatment resistant clients or facilitate additional improvement following poor treatment response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Mennin and Fresco (2013) summarized empirical evidence suggesting that (1) comorbid anxiety and mood disorders are associated with greater rumination (Olatunji et al, 2013), and (2) those with comorbid anxiety and depression often have the poorest response to treatment (e.g., Farabaugh et al, 2010). As such, the authors suggest that those with high RNT may be least likely to respond to traditional CBT and may benefit from specifically targeting RNT in treatment (Mennin & Fresco, 2013). Thus, RNT-focused intervention may improve outcome for treatment resistant clients or facilitate additional improvement following poor treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…Others have found that rumination is associated with delayed symptom remission in mild-moderately depressed participants (Jones, Siegle, & Thase, 2008) and greater likelihood of relapse following mindfulness based cognitive behavior therapy (Michalak, H€ olz, & Teismann, 2011). Such poor treatment response and lack of durable treatment effects associated with RNT have prompted the suggestion that RNT may be an endophenotype of treatment refractory patients who would benefit from personalized treatment (Mennin & Fresco, 2013).…”
mentioning
confidence: 99%
“…De manera que, los tratamientos efectivos alientan las estrategias adaptativas de regulación emocional y desalientan el uso de estrategias ineficaces. Tanto la rumiación como la preocupación son ejemplos de procesos cognitivos de regulación emocional transdiagnósticos que se asocian a efectos negativos desadaptativos (mennin & Fresco, 2013;Segerstrom, Tsao, Alden & Craske, 2000).…”
Section: Conclusiónunclassified
“…A raíz de esta tendencia, se han encontrado mejoras significativas en el tratamiento de los trastornos del estado de ánimo como la ansiedad o la depresión (Aldao et al, 2010), por lo que la investigación ha aumentado el foco sobre los constructos que comportan están técni-cas (Eisenlohr-Moul, Peters, & Baer, 2015). Estas nuevas líneas de investigación están ayudando a explicar y comprender estos constructos y su relación con aquellas variables que comportan una buena salud psicológica (Ciesla, Reilly, Dickson, Emanuel, & Updegraff, 2012;Mennin & Fresco, 2013). La idea de la salud psicológica está compuesta por dimensiones psicológicas positivas y negativas, entre las cuales se encuentra la satisfacción con la vida que a su vez se postula como una de las más importantes para determinar la percepción de bienestar en del individuo (Ford, Lam, John, & Mauss, 2017).…”
Section: Antecedentesunclassified